Vaned recess anti-stall for axial-flow fans and compressors - Kang, Chang (Cranfield University, 1996)
The study of anti-stall techniques for fans and compressors has never been more significant, since the potential applications were recognised in gas turbines, tunnel ventilation (jet fans) and industrial process where fans/compressors would benefit from the devices. This thesis will discuss the techniques achieving competitiveness by modifying the conventional casing design of the fan and compressor, which is referred to as casing treatments, taking into account the change of maximum efficiency and flow range. An experimental investigation to examine the influence of the vaned recess casing treatment on stall margin, operating efficiency and flow field of a low speed axial flow fan with aerospace type blade loading is presented. Different geometrical designs of the vaned passages were examined and more than 65% of stall margin improvements and over twice pressure rise with insignificant peak efficiency change were obtained. Experiments to examine the effect of casing treatments on the flow field were carried out using the same fan rig with a tip clearance of 1.2% of the blade height. A high frequency data acquisition system including both hardware and software was developed and the 3-D flow measurements with a slanted hot-wire were undertaken. The first detailed results of flow measurements associated with the vaned recess casing treatment are presented, including both time-averaged and ensemble-averaged measurement results. The flow features in both the solid casing and treated casing builds are captured and comparison between the builds presented. The results revealed that the stall margin improvement due to the casing treatment was not achieved by reducing the incidence nor by increasing the total pressure in the tip region. It appeared that the combined functions of elimination of the whirling flow, the removal of the randomness of the inlet flow and modification of the tip clearance flow are salient features associated with the mechanism of the treatment. The steady flow field of the test fan with various tip clearances has also been simulated in the rotating frame with computational fluid dynamics (CFD) to investigate the clearance effect on the end-wall flow development and to elucidate the behaviour of the tip leakage flow, and hopefully shed more light onto the flow phenomena involved.